If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -7 = 2x + -3 Reorder the terms: -7 + x = 2x + -3 Reorder the terms: -7 + x = -3 + 2x Solving -7 + x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -7 + x + -2x = -3 + 2x + -2x Combine like terms: x + -2x = -1x -7 + -1x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 -7 + -1x = -3 + 0 -7 + -1x = -3 Add '7' to each side of the equation. -7 + 7 + -1x = -3 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = -3 + 7 -1x = -3 + 7 Combine like terms: -3 + 7 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4
| 13+3x-9=10x-14-5x | | -9=108 | | 3x^2-3=45 | | x^2-24x+1=0 | | 100(x-3)=450-50 | | t/3-2=9 | | -6(8+6k)=-228 | | 7/5(40) | | x+7/5x=96 | | 6d/4=24 | | -153-12x=71+2x | | -5+7=5x-4(x-1) | | 9Y-1=y-5 | | D(3-7)-12=0 | | 6m/7-3=9 | | -82-3x=11x+170 | | 7m-10m=27 | | .5=.09 | | 9(w-4)=7w-44 | | 3+573g=3g | | 3+573=3g | | 3m^3-32m-8=0 | | 3+573=g | | 3a+3a=16+18a | | an=-7+6 | | -98-3x=98-10x | | .66t+4=2 | | 4096=r^6 | | 2x+5y=-34 | | t=96t-16t^2 | | l=5+2x | | 4-6w=3*1/2+w/2 |